1994
DOI: 10.1143/jjap.33.4566
|View full text |Cite
|
Sign up to set email alerts
|

Filling of Sub-µm Through-holes by Self-sputter Deposition

Abstract: Filling of sub-µ m holes with a high aspect ratio by self-sputter deposition of copper is investigated. Good bottom coverages of 100% by means of thinner thin-film deposition and 50% by thicker thin-film deposition are attained. It is found that the bottom coverage decreases sharply when the ratio of the distance between the target and the substrate, D st, to the diameter of the erosion center ring is less than 1, and although the bottom coverage by the self-sputter deposition at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Sputtering is an alternative to electroplating as a Cu filling method. [8][9][10][11][12][13] Sputtering has the advantages of producing highly reliable results since the era of Al wiring and being accomplished with equipment that is easy to operate. Even now, it is used to form trench barrier layers 14,15) and Cu seed layers.…”
Section: Introductionmentioning
confidence: 99%
“…Sputtering is an alternative to electroplating as a Cu filling method. [8][9][10][11][12][13] Sputtering has the advantages of producing highly reliable results since the era of Al wiring and being accomplished with equipment that is easy to operate. Even now, it is used to form trench barrier layers 14,15) and Cu seed layers.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, the PVD technology has been continuously improved for a long time. [4][5][6][7][8][9][10][11][12][13] To obtain a high bottom and side coverage, it is necessary to increase the ionization ratio, and then a self-ionization sputtering (SIS) method has been developed because Ar gas is not injected during the sputtering process and the discharge is maintained only by Cu atoms. Recently, Sakamoto et al have reported that the number of Cu ions incident to the substrate was increased by magnetic-field-assisted ionized sputtering (MFIS) and the step coverage and asymmetric profile were improved.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In this process, the Ar was only used for ignition and was shut off afterwards. Magnetron sputter deposition is widely used for metal deposition due to its simplicity, low cost, and high purity.…”
Section: Introductionmentioning
confidence: 99%